Drills and holes – pottery repairing as evidence of the social meaning of an object. (20th December 2020) - Miloglav, Ina
Abstract: In addition, to reconstruct and fully understand operational and behavioural chain in the life-cycle of an artefact it is essential to consider marks that indicate the life of an artefact in a secondary context, where it can no longer be used for the primary function. Reused objects affect the total assemblage interpretation and have to be considered as part of the technological, economic, social and ideological context. Those marks are especially recognizable in repairing the pottery, which is a very good indicator of adoption of pottery to new purposes and changing its value for the owner or entire community. The paper presents results and interpretation of pottery repairs from two sites in Eastern Croatia belonging to the Vučedol Culture (Late Copper Age). The results have shown that the most frequently repaired form is the type of bowl which have the highest rate of standardization, production and use. These bowls also require more labour input, and they are time-consuming for the potters. Their value is not only in economic need for a specific product but probably in a combination of social, aesthetic and technological values.